1985
DOI: 10.1007/bf01476216
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of cerebral vasospasm with OKY-046 an imidazole derivative and a thromboxane synthetase inhibitor. A preliminary co-operative clinical study

Abstract: The prevention of cerebral vasospasm with OKY-046, an imidazole derivative and a thromboxane synthetase inhibitor, was studied co-operatively at ten neurosurgical services. Intravenous administrations of 2, 5 or 10 mu/kg/minute of OKY-046 were given continuously from the earliest possible day to the 14th SAH-day to 82 patients with ruptured cerebral aneurysm. Sixty-eight patients (83%) showed moderate to high high-density (SAH) in their initial CTs. Angiographic vasospasms were seen in 58 patients, representin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

1987
1987
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…However, clinical experiences of patients with asymptomatic cerebral vasospasm and with ischemic symptoms with rather mild vaso spasms34) prompted us to consider the involvement of some intraluminal factors in peripheral vessels. Recently, it has been reported that an imbalance in the synthesis of thromboxane A2 (TXA2) and pros tacyclin (PGI2), in favor of TXA2i2,1s,2'> and blood hypercoagulability11,37,38,40) must be involved in this pathogenesis, that the preventive effect of TXA2 synthetase inhibitor was more evident for cerebral ischemic symptoms than for vasospasms per se, 8, 30,32,34,36) and that other antiplatelet drugs are also effective for prevention of this syndrome. 6,23,38) Con sideration of these reports suggests that thrombus formation, particularly due to platelet aggregation, may be a decisive factor in inducing cerebral ischemia in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical experiences of patients with asymptomatic cerebral vasospasm and with ischemic symptoms with rather mild vaso spasms34) prompted us to consider the involvement of some intraluminal factors in peripheral vessels. Recently, it has been reported that an imbalance in the synthesis of thromboxane A2 (TXA2) and pros tacyclin (PGI2), in favor of TXA2i2,1s,2'> and blood hypercoagulability11,37,38,40) must be involved in this pathogenesis, that the preventive effect of TXA2 synthetase inhibitor was more evident for cerebral ischemic symptoms than for vasospasms per se, 8, 30,32,34,36) and that other antiplatelet drugs are also effective for prevention of this syndrome. 6,23,38) Con sideration of these reports suggests that thrombus formation, particularly due to platelet aggregation, may be a decisive factor in inducing cerebral ischemia in this syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…Vasospasm was demonstrated by angiography in nine of these cases, but only two of the nine showed mild signs of cerebral ischemia, which suggests the significance in symptomatic vasospasm of thrombus formation by platelet aggregation and the effectiveness of trapidil as a preventive agent [76]. They also tried OKY-046, an imidazole derivative and a thromboxane syntheses inhibitor; it was studied cooperatively at ten neurosurgical services [77] or at 48 neurosurgical services in Japan in double-blind fashion [78]. Both trials showed the usefulness of OKY-046 for the prevention of symptomatic vasospasm and support the hypothesis that cerebral microthrombosis plays an important role in the pathogenesis of cerebral vasospasm.…”
Section: Microthrombosismentioning
confidence: 99%
“…On this baSis recently Suzuki et al 33 reported preliminary results of a clinical trial designed to verify the possibility to reduce the extension of ischaemic complications due to vasospasm following SAH, using thromboxane synthetase inhibitors. Moreover, some authors15, 17, 27 have discussed the cisternal wash-out during aneurysm surgery as a practical method of reducing the incidence of vasospasm: our findings suggest that cisternal wash-out could suddenly reduce the biochemical reactions that trigger vasospasm, but could not interfere with the prolonged abnormal synthetic activity of the arterial wall, as shown in the cisternal CSF samples obtained 15-20 days after the haemorrhage.…”
Section: Discussionmentioning
confidence: 97%